Análisis y diseño de las políticas públicas - Neira, Idaluz (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2023)
From the perspective of the public-private relationship, it is worth remembering that what is public exceeds the scope of the state, with similarities, coincidences in the contexts, referred to from the breadth with which an action is carried out to forms of relationship that go beyond the individual, but they are not determined or protected by the state. This text seeks to provide general guidelines for the formulation and design of these public policies from the perspective of democracy and equality, a sociological and practical analysis.